Typhonium trilobatum (L.) Schott: Phytochemistry, Traditional Uses and It’s Anti Inflammatory Activity - Sarwade, Prakash Pralhad; Gaisamudre (Sarwade), Kavita Narayan; Bhise, Damaji Shankar; Kumar S.R., Santosh; Maurya, Chandresh; Vishwakarma, Pratik Kumar (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Typhonium trilobatum (L.) Schott, a Araceae family plant less known but has been used traditionally for long by indigenous and folk practitioner’s throughout South and Southeast Asia. It was applied in the treatment of inflammatory conditions, venomed bites, wounds and respiratory disorders principally in the use of the plant and in particular its underground tuber. Although it had been traditionally used in medicine until recently, modern scientific evaluation of its phytochemical and pharmacological properties is coming on stream. The anti-inflammatory activity and the ethnomedicinal uses of the Typhonium trilobatum are summarized with current knowledge on its phytochemistry to bring about the possibility on being natural therapeutic agent. Pharmaceutical study shows that the plant is rich it contains alkaloids; flavonoids; saponins; phenolic acids; tannins; terpenoids; steroids. The constituents of these are well known to have strong anti inflammatory, antioxidant, antimicrobial and analgesic properties. Methanolic and aqueous extracts have been demonstrated to possess the potential for anti inflammatory activity in experimental models by significantly reducing edema and denaturing protein. The review also emphasises the need to validate traditional knowledge using scientific research, especially in medicinal plants like T. trilobatum which are not well investigated. Preliminary studies however are promising and more in depth research is needed to isolate active constituents, explain mechanisms of action and assess safety profiles. Thus, with the escalating interest in plant based alternatives to synthetic anti inflammatory drugs Typhonium trilobatum holds considerable potential as a sustainable source for future therapeutic development. An attempt is herein made to bridge the gap between ethnomedicine and pharmacological science of this traditionally royalty venerated plant by this review which should stimulate further investigation into its medicinal potential.